(untitled) (Journal of Architectural Design, 2022)
The paper considers a new approach to the design of preschool institutions, taking into account the psychology of children’s perceptions. The basic principles of creating the environment, motivating children to study, and developing their mental, creative and physical abilities were identified. Buildings of preschool institutions are seen as means of the world perception and social adaptation of children. The child perceives the world through visual, tactile and other sensations. All factors of changing the world should be reflected in the architectural style of a building